Sero-Prevalence of Porcine Reproductive and Respiratory Syndrome (PRRS) in Pigs of Different Developmental Regions of Nepal - K.C., Mahesh; Joshi, Bhoj Raj; Shrestha, Swoyam Prakash; Prajapati, Meera; Kathayat, Dipak; Dhakal, Santosh (International Journal of Applied Sciences and Biotechnology, 2015)
Porcine reproductive and respiratory syndrome (PRRS) is a highly infectious viral disease of swine. This disease is becoming threat to pig industry of every corner of the world. As the status of this disease in Nepal is not properly understood so far, a cross-sectional sero-prevalence study was carried out in four development regions. A total of 200 blood samples were collected from major pig producing areas of eight districts of four development regions of Nepal and the serum samples were tested for antibodies against PRRS virus by rapid antibody detection kit (Immunochromatographic test using colloidal gold immunoassay: Schenzhen Lvshiyuan biotechnology Co. Ltd, China). Among the tested serum samples, 37 were found to be positive for PRRS indicating 18.5% prevalence of the disease. Statistically the prevalence difference was significant between different development regions and between topographical regions (P<0.05) of the country, but no significant difference was observed in age, sex and housing systems of pigs. Presence of antibodies in serum against PRRSV in the unvaccinated pig population of the country clearly indicates that pigs of the surveyed regions of Nepal have already been exposed to PRRS virus and the disease should be given adequate attention during differential diagnosis of porcine respiratory diseases in Nepal. Further studies are needed for molecular characterization of the virus and to develop control strategies against this disease in the country. Int J Appl Sci Biotechnol, Vol 3(2): 218-222 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12539